Crop-Livestock-Forestry Integration in Brazil:: a sustainable agriculture strategy based on the concepts of Green Economy Initiative - Reis, Julio; Rodrigues, Renato; Conceição, Marcela; Martins, Carolinna (Sustainability in Debate, 2016)
This article proposes to transform the current production model through the organization of an agricultural system based on the concepts of crop-livestock-forestry integration (ICLF). We used the guidelines and concepts related to the Green Economy Initiative (GEI), a proposal of the United Nations Environment Program (UNEP). Within this framework, the agricultural sector is identified as an important sector due to its strong connection with economic, social and environmental dimensions. We intend to demonstrate that the ICLF proposal is in line with aspects of sustainable agriculture, as proposed by GEI, and that it is an important strategy to increase production in a sustainable manner in Brazil. The adoption of GEI is a consistent strategy for the implementation of policies to promote sustainable development.